2020
DOI: 10.1021/jacs.0c07976
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Encoding of para-Pentafluorosulfanyl Phenylalanine: A Highly Hydrophobic and Strongly Electronegative Group for Stable Protein Interactions

Abstract: SF5Phe, para-pentafluorosulfanyl phenylalanine, is an unnatural amino acid with extreme physicochemical properties, which is stable in physiological conditions. Here we present newly developed aminoacyl-tRNA synthetases that enable genetic encoding of SF5Phe for site-specific incorporation into proteins in high yields. Owing to the SF5 moiety’s dichotomy of strong polarity and high hydrophobicity, the unnatural amino acid forms specific and strong interactions in proteins. The potential of SF5Phe in protein re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…In addition, the C-terminal Mm PylRS domain contained the mutation Y384F (in the sequence numbering of the wild-type enzyme) reported to increase the aminoacylation activity of PylRS . The final library plasmid pBK-ChPylRS encoded the ChPylRS mutants, where the residues A302, L305, Y306, N346, C348, and V401 of the substrate binding pocket were fully randomized, and an orthogonal Mb tRNA CUA Pyl in a pBK vector . Another selection plasmid, pBAD-H6RFP, contained a mCherry red fluorescent protein (RFP) gene following a His 6 -tag and amber stop codon.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the C-terminal Mm PylRS domain contained the mutation Y384F (in the sequence numbering of the wild-type enzyme) reported to increase the aminoacylation activity of PylRS . The final library plasmid pBK-ChPylRS encoded the ChPylRS mutants, where the residues A302, L305, Y306, N346, C348, and V401 of the substrate binding pocket were fully randomized, and an orthogonal Mb tRNA CUA Pyl in a pBK vector . Another selection plasmid, pBAD-H6RFP, contained a mCherry red fluorescent protein (RFP) gene following a His 6 -tag and amber stop codon.…”
Section: Resultsmentioning
confidence: 99%
“…Scheme 67 Synthesis of meta-SF5 stavudine (d4T) ProTide 59 An innovative use the SF5 group in biological chemistry was recently proposed by Huber et al who developed aminoacyl-tRNA synthetases enabling genetic encoding of SF5-Phenylalanine (Figure 6) for site-specific and high-yielding incorporation of this unnatural amino acid into proteins. 60 The authors demonstrated the capacity of SF5-Phe to form specific and strong interactions in proteins. Of particular interest was the replacement of two Phe residues with SF5-Phe in the core of Escherichia coli's peptidyl-prolyl cis/trans-isomerase B, which demonstrated the viability of the method for functionalizing proteins with SF5 groups for structural biology and in vivo studies.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…143,144 More recently intramolecular NOEs were observed between two pentafluorosulfonyl-substituted phenylalanines in a folded protein. 145 19 F paramagnetic relaxation enhancement (PRE) experiments complement NOE experiments with longer range information. The Gronenborn lab has showed this technique to give structural information over distances of 12-24 Å, which is comparable to 1 H PRE (13-25 Å).…”
Section: Quantification Of Binding Interactions In Intermediate and Slow Exchangementioning
confidence: 99%
“… 143,144 More recently intramolecular NOEs were observed between two pentafluorosulfonyl-substituted phenylalanines in a folded protein. 145 …”
Section: Protein-observed 19 F Nmrmentioning
confidence: 99%